Pengembangan E-Modul berbasis Model Problem-Based Learning untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Dasar Program Keahlian Kelas X TKJ di SMK Negeri 5 Malang - Ervina Nurhidayati; Satrio Hadi Wijoyo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Education functions as a disclosure of information in the form of values, knowledge, and skills by educators to students. Education is more than just teaching. So that it can be said as an effort to transfer information, change values, and shape character from all the perspectives it covers. However, based on the observation activities by researchers in class X TKJ SMK Negeri 5 Malang on Dasar Program Keahlian subjects, various problems were found that invited the attention of researchers to solve them. These problems resulted in the low learning outcomes of class X students of TKJ SMK Negeri 5 Malang class of 2021 in Dasar Program Keahlian subjects. Teaching materials in module format are teaching materials that prioritize user independence, efficiency, and effectiveness. Modules are material associations that highlight instructional abilities. As technology advances, modules can also be introduced in advanced designs called e-modules. The development of e-modules with the Problem-Based Learning model applies the ADDIE method in the development process. The ADDIE model can be used to describe a systematic procedure for developing a product. ADDIE was developed by Reiser and Mollanda which is a collection of abbreviations that are guided by the main procedures of the development process.